The Efficiency of Implementing the Interpretive Perspective in Teaching English in Algeria Case of Middle and High School Textbooks - Betka Rezig, Nadia (University of Eloued جامعة الوادي, 2016)
The Algerian English textbooks designed for middle and high school levels present the cultural information about the foreign language speaking communities through an interpretive perspective or a trans-cultural information using universal categories of human behavior and the learner is expected to relate and interpret the information and evaluate it. If the learner is not provided with a key to interpret phenomena with the local culture, the interpretive approach outcomes can not be fulfilled and the learner will be introduced to much knowledge without learning a specific information. Following Vygotsky‘s view on learners‘ Proximal Zone Development, the teaching of second and foreign languages should implement a task based curriculum to introduce information and to generate learners‘ cognitive abilities being problem solvers rather than passive learners. The interpretive perspective presents a wide range of varied cultural information but it must be supported with tasks and exercises that can develop learners‘ critical thinking that prepares them for more advanced knowledge at university level; for instance, in learning literature. The present study presents data gathered from a questionnaire administered to first year university English learners and a language proficiency test (written and oral) they sat for. The two research instruments were used respectively, to collect data on English learners‘ attitude towards English and its culture as well as the main deficiencies that these learners present as far as critical skills such as comparison, interpretation, analysis and opinion gaps are concerned. The results showed that English learners arrive at university carrying a positive attitude towards the English culture though they recognize the excessive differences between the local and the foreign language cultures and present a serious deficit in cultural critical skills visible through their achievement in the oral and written tests.
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued
Keywords: The Efficiency of Implementing , Interpretive Perspective in Teaching English , Algeria, Middle and High School Textbooks